Neurofilament light compared to neuron-specific enolase as a predictor of unfavourable outcome after out-of-hospital cardiac arrest. (May 2022) - Wihersaari, L.; Reinikainen, M.; Furlan, R.; Mandelli, A.; Vaahersalo, J.; Kurola, J.; Tiainen, M.; Pettilä, V.; Bendel, S.; Varpula, T.; Latini, R.; Ristagno, G.; et al.
Abstract: Aim: We compared the prognostic abilities of neurofilament light (NfL) and neuron-specific enolase (NSE) in patients resuscitated from out-of-hospital cardiac arrest (OHCA) of various aetiologies. Methods: We analysed frozen blood samples obtained at 24 and 48 hours from OHCA patients treated in 21 Finnish intensive care units in 2010 and 2011. We defined unfavourable outcome as Cerebral Performance Category (CPC) 3–5 at 12 months after OHCA. We evaluated the prognostic ability of the biomarkers by calculating the area under the receiver operating characteristic curves (AUROCs [95% confidence intervals]) and compared these with a bootstrap method. Results: Out of 248 adult patients, 12-month outcome was unfavourable in 120 (48.4%). The median (interquartile range) NfL concentrations for patients with unfavourable and those with favourable outcome, respectively, were 689 (146–1804) pg/mL vs. 31 (17–61) pg/mL at 24 h and 1162 (147–4360) pg/mL vs. 36 (21–87) pg/mL at 48 h, p < 0.001 for both. The corresponding NSE concentrations were 13.3 (7.2–27.3) µg/L vs. 8.5 (5.8–13.2) µg/L at 24 h and 20.4 (8.1–56.6) µg/L vs. 8.2 (5.9–12.1) µg/L at 48 h, p < 0.001 for both. The AUROCs to predict an unfavourable outcome were 0.90 (0.86–0.94) for NfL vs. 0.65 (0.58–0.72) for NSE at 24 h, p < 0.001 and 0.88 (0.83–0.93) for NfL and 0.73 (0.66–0.81) for NSE at 48 h, p < 0.001. Conclusion: Compared to NSE, NfL demonstrated superior accuracy in predicting long-term unfavourable outcome after OHCA.